A test of the reliability of estimating menarcheal status in juvenile remains from dental and skeletal maturation - Ilkhan, T.; Goodarzi, P.; Andrade, M. A. P.; Cardoso, Hugo F. V. (51st Annual Meeting of the Canadian Association for Biological Anthropology, 2024)
While bioarchaeologists are starting to appreciate and develop approaches to the study of puberty and adolescence in past populations, there is still limited research on how to estimate sexual maturation from skeletal and dental observations. This study addresses this gap by using logistic regression to examine the relationship between menarcheal status (pre- or post-menarche) and skeletal and dental maturation in a longitudinal sample of 34 French-Canadian girls aged 6 to 19 from the University of Montreal Growth Study. Dental maturation was assessed using Demirjian’s stages, while skeletal maturation was evaluated using the hand-wrist Tanner-Whitehouse technique. The results identified the distal radius and the lateral incisor as the strongest predictors of menarcheal status. Models generated from the radius were used to determine pre- and post-menarcheal status on a known sex and age skeletal sample of adolescent girls (n=23) between 10 and 18 years of age from the Lisbon skeletal reference collection, housed at the National Museum of Natural History and Science in Lisbon, Portugal. The age of menarche was then estimated from this skeletal sample by using logistic regression. The mid-point between the distribution of pre- and post-menarcheal status girls was used as the median age of menarche in the population. The estimated age of menarche in this sample (~14 years of age) compares well with published research about the mean age of menarche carried out at the time the girls in the skeletal sample lived in Lisbon (1920-1940). This indicates that the approach provided here can estimate menarche in archaeological populations and be added to the bioarchaeologist’s toolbox. While this methodology has a significant caveat associated with the unreliability of sex estimation in adolescent skeletons, it has the potential to provide important insight into reproductive health and the social and nutritional conditions of past populations.